Membangun Kesadaran Inklusifmultikultural untuk Deradikalisasi Pendidikan Islam - Andik Wahyun Muqoyyidin (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2013)
There are still many acts of terrorism that are as concrete evidence of how the use of the security approach alone isn’t effective enough to eradicate terrorism and Islamic radicalism to its roots in Indonesian. Therefore, various approaches to handling terrorism and Islamic radicalism must also be constantly pursued. That is the de-radicalization program through the nuances of Islamic education multicultural inclusiveness. In this case, they should pay attention to curriculum factors, educators, and educators use learning strategies.